Beobachtung, Begegnung und Beziehung: die Bildung von Marktintelligenz in der globalen Agenturfotografie = Observation, encounter and relationship : the acquisition of market intelligence in stock photography - Glückler, Johannes; Panitz, Robert (Zeitschrift für Wirtschaftsgeographie, 2015)
The increasing global extension of the division of creative labour challenges remote firms to develop the market intelligence necessary to satisfy demand preferences of spatially distant customers. We distinguish four socio-material situations of learning where each situation implies a specific combination of three basic social communication technologies: observation (Beobachtung), encounter (Begegnung), and relationship (Beziehung). This paper assesses the empirical importance of these communication technologies for the acquisition of market intelligence in stock photography, a sector of the creative industries. Our analysis is based on a unique global survey of the stock photo market as well as interviews with picture agencies conducted at several international congresses. Our findings demonstrate that picture agencies develop market intelligence predominantly through observation and relationships over distance rather than through temporary encounter. Although congresses and trade fairs have grown in number and size over the last decades, their primary function can be defined as a social relay: During congresses, picture agencies organize innumerable appointments to rewire their global partnerships which then, after being set in practice, become sources of relational market intelligence.
Gesehen am 04.06.2020